2014
DOI: 10.1007/s12098-014-1442-3
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Severe Hyperparathyroidism due to Compound Heterozygous Mutation of Calcium Sensing Receptor (CaSR) Gene Presenting as Encephalopathy

Abstract: The authors report a 14-d-old neonate who presented with lethargy, polyuria and dehydration and was found to have severe hypercalcemia with hyperparathyroidism. This neonate was treated with saline hydration, diuresis and injection pamidronate. Genetic analysis revealed a compound heterozygous mutation of CaSR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…showed that the neonates presented in the first month of life, one treated medically and the other maintained on medical management after failed surgery, suggesting a role for prolonged medical management. [ 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…showed that the neonates presented in the first month of life, one treated medically and the other maintained on medical management after failed surgery, suggesting a role for prolonged medical management. [ 16 17 ]…”
Section: Discussionmentioning
confidence: 99%